Roles of supporting cells in the maintenance and regeneration of the damaged inner ear: A literature review - Jing-Ying Guo; Jun-Yi Xu; Shu-Sheng Gong; Guo-Peng Wang (Journal of Otology)
The inner ear sensory epithelium consists of two major types of cells: hair cells (HCs) and supporting cells (SCs). Critical functions of HCs in the perception of mechanical stimulation and mechanosensory transduction have long been elucidated. SCs are indispensable components of the sensory epithelia, and they maintain the structural integrity and ionic environment of the inner ear. Once delicate inner ear epithelia sustain injuries (for example, due to ototoxic drugs or noise exposure), SCs respond immediately to serve as repairers of the epithelium and as adapters to become HC progenitors, aiming at morphological and functional recovery of the inner ear. This regenerative process is extensive in non-mammals, but is limited in the mammalian inner ear, especially in the mature cochlea. This review aimed to discuss the important roles of SCs in the repair of the mammalian inner ear.